The distribution of ammonia on Jupiter from a preliminary inversion of Juno microwave radiometer data. Issue 11 (3rd June 2017) - Li, Cheng; Ingersoll, Andrew; Janssen, Michael; Levin, Steven; Bolton, Scott; Adumitroaie, Virgil; Allison, Michael; Arballo, John; Bellotti, Amadeo; Brown, Shannon; Ewald, Shawn; Jewell, Laura; et al.
Abstract: The Juno microwave radiometer measured the thermal emission from Jupiter's atmosphere from the cloud tops at about 1 bar to as deep as a hundred bars of pressure during its first flyby over Jupiter (PJ1). The nadir brightness temperatures show that the Equatorial Zone is likely to be an ideal adiabat, which allows a determination of the deep ammonia abundance in the range 362 − 33 + 33 ppm. The combination of Markov chain Monte Carlo method and Tikhonov regularization is studied to invert Jupiter's global ammonia distribution assuming a prescribed temperature profile. The result shows (1) that ammonia is depleted globally down to 50–60 bars except within a few degrees of the equator, (2) the North Equatorial Belt is more depleted in ammonia than elsewhere, and (3) the ammonia concentration shows a slight inversion starting from about 7 bars to 2 bars. These results are robust regardless of the choice of water abundance. Plain Language Summary: The distribution of ammonia gas on Jupiter's atmosphere was derived by fitting the microwave spectra measured by the Juno spacecraft. The result showed that the concentration of ammonia gas in the extratropics was much less than expected and had a local minimum near 7 bars of pressure. Key Points: Jupiter's deep ammonia abundance is estimated using nadir brightness temperatures Ammonia gas concentration is depleted with respect to the deep value down to at least 50 bars outside of the Equatorial Zone An ammonia‐rich zone occupies 0‐5°N and extends from the deep atmosphere to the base of the ammonia cloud.